Intrathecal T‐cell clonal expansions in patients with multiple sclerosis. Issue 6 (20th April 2016) - de Paula Alves Sousa, Alessandra; Johnson, Kory R.; Nicholas, Richard; Darko, Sam; Price, David A.; Douek, Daniel C.; Jacobson, Steven; Muraro, Paolo A.
Abstract: Objective: Analysis of the T‐cell receptor (TCR) repertoire in the cerebrospinal fluid (CSF) of patients with multiple sclerosis (MS) can reveal antigen‐specific immune responses potentially implicated in the disease process. We applied a new unbiased deep‐sequencing method for TCR repertoire analysis to accurately measure and compare receptor diversity and clonal expansions within the peripheral and CSF‐trafficking T‐cell populations of patients with MS and control individuals with idiopathic intracranial hypertension (IIH). Methods: Paired blood and CSF TCR β ‐chain libraries from five MS patients and five IIH controls were sequenced, yielding a total of 80 million reads. Results: Although TCR repertoire diversity was greater in the blood and CSF compartments of MS patients when compared with IIH controls, it is notable that the frequency of clonal expansions was also significantly higher in both compartments of MS patients. Highly expanded T‐cell clones were enriched in the CSF compartment of MS patients compared to peripheral blood, very few of them were detected in both compartments. Interpretation: Collectively, our data provide a proof of principle that private compartmentalized T‐cell expansion exists in the intrathecal space of MS patients.